Antibacterial Activity tof Taro Leaf Stalk Ethanol Extract (Colocasia esculenta) against Acne-Causing Bacteria - Irianti, Ewith Ratih; Ramadhani, Lidia Anggita; Ramadhan, Firdaus; Noor, Susan Maphilindawati; Syafriana, Vilya (Jurnal Sumberdaya Hayati, 2025)
Acne is a skin disease caused by several factors, including infection with Staphylococcus epidermidis bacteria. Natural compounds have been used to reduce side effects from anti-acne drugs. Colocasia esculenta has been found effective as a drug and potential antibacterial agent. This research aimed to determine the antibacterial activity of C. esculenta leaf stalk ethanol 70% extract against S. epidermidis and its bioactive compound. The extract was produced using the maceration method. The antibacterial activity was tested using the disk diffusion method with concentrations of 0.5, 1, 1.5, 2, and 2.5%, and clindamycin was used as a positive control. The clear zone was measured for antibacterial activity data interpretation. The results showed a clear zone at all concentrations except 0.5%, with values of 17.33, 20, 25, and 27.67 mm, respectively. The clear zone value for the positive control was 47 mm. Phytochemical screening of the taro leaf stalk ethanol 70% extract had positive results for all phytochemical tests. The results indicate that Colocasia esculenta leaf stalk ethanol 70% extract is potentially an antibacterial against S. epidermidis and contains other bioactive compounds.